Analysis and applications of the molecular typification of the mitochondrial genome of Beauveria bassiana - URIBE, DANIEL; KHACHATOURIANS, GEORGE (Revista Colombiana de Entomología, 2007)
Beauveria bassiana is one of the entomopathogenic fungi most widely used world wide for the control of insect pests in the agricultural sector. Its importance from the commercial point of view has lead to the necessity to develop strategies of molecular characterization, with the aim of following the fate of strains in the field and eventually protecting those that are most commercially important. The mitochondrial genome is a tool that is appropriate for taxonomic characterization, the development of phylogenetic studies and the characterization of strains at the molecular level because it is a haploid molecule, fast evolving and with functional similarity at different taxonomic levels. In this work the mitochondrial DNA diversity of 20 strains of the entomopathogenic fungi B. bassiana were evaluated. This characterization was done by using the RFLP technique with the total mitochondrial DNA of the standard strain GK2016 digested with the restriction enzyme Hpa II as a probe. A great diversity was found, represented by the presence of 10 mito-types within the sample studied. No specific relationship was found between the patterns of mito-typification and either the geographic origin or the host. Similarly a phylogenetic analysis was conducted on several filamentous fungi species including some entomopathogenic fungi using the mitochondrial gene 16s srRNA. The analysis of these results and our interpretation of the implications for research on B. bassiana are discussed.